Leaves per tiller as the criterion to determine optimum defoliation frequency in pastures of Brachiaria decumbens - Diana Leidy Manrique Luna; Juan Evangelista Carulla Fornaguera (Revista Facultad Nacional de Agronomía Medellín, 2020)
Two studies were performed to establish the best defoliation frequency in Brachiaria decumbens using the number of leaves per tiller as a criterion. In the first study, 3,500 tillers with 2, 3, 4, 5, or 6 leaves were collected in 10 farms. The number of green, senescent, and dead leaves was counted. A pooled sample of tillers by each farm with a given number of leaves was analyzed for nutritional quality; a complete randomized block design was used for this study. In a second study, it was implemented a complete ramdomized design with repeated measures over time (2 defoliations), and the effect of defoliating B. decumbens at 3, 4, or 5 leaves per tiller on its growth, dry matter yield, and nutritional quality were evaluated. In the first study, all leaves remained green until the tiller had 3 leaves. At the fourth leaf, few tillers (2.3%) had senescent leaves, but at 6 leaves, most tillers had senescent (40.6%) or dead (24.4%) leaves. Crude protein and digestibility decreased as the number of leaves in a tiller increased (P<0.001). In the second study, the rate of dry matter accumulation was the highest for plots defoliated at 4 leaves (P<0.05). Green stems (43.9%) represented a larger proportion of dry matter than green leaves (31.4%), and their proportions were similar among treatments. Crude protein and digestibility of stems decreased as the number of leaves per tiller increased (P<0.001), but the quality of leaves was similar. These findings suggest that these pastures should be defoliated at 4 leaves per tiller.